ANALISIS BEBAN KERJA PADA KANTOR CABANG PELAYANAN DINAS PENDAPATAN DAERAH WILAYAH KOTA BOGOR - Juliefte, Feranny; Purnamasari, Irma; Pratidina, Ginung (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2015)
The research aimed to know the implementation workload, the barriers of implementation workload and the efforts made in the implementation of the workload at the Branch Office Revenue Service Office of the Provincial Bogor City Region. Methods Used was survey research. The types of data used were the primary and secondary data. Primary data was collected by spreading questionnaire, and supported by the observations and interviews. The collection of secondary data sourced from documents, libraries and related writings. Sampling Technique: The research population amounted to 23 respondents in the Branch Office Revenue Service Office of Bogor City Region. on the workload analysis at the Office of Personnel Services Branch Office of the Provincial Revenue Bogor City Region can be concluded although there was a delay only requirements factor and completeness of the taxpayer that were less satisfied however, it did not affect the overall performance. The volume of work could be obtained information about the efficiency and effectiveness of the organization, and had the objective to the achievement of public service in minimizing the public complaints in particular taxpayer and effective working hours in work standards was a guide or guidance of each employee to complete the appropriate time in order to carry out tasks to provide certainty and clarity of the process and provide legal certainty to the public, especially taxpayers.Â Keywords: Workload, Work Volume, Norm of Effective Time and Effective Working Hours